Analisis Tingkat Kepuasan Konsumen terhadap Pelayanan Bongkar-Muat Barang pada Terminal Petikemas Semarang - Janto, Yoeli (Department of Civil Engineering, Diponegoro University, 2014)
This study aims to analyze the level of consumer expectations and service performance and user satisfaction level loading service at Semarang Container Terminal. It also analyzes the factors that must be maintained, high priority, low priority and customer satisfaction excessive loading and unloading of goods at the Container Terminal in Semarang. The samples are 73 respondents (companies) with data analysis using the Important Performance Analysis (IPA). Based on the analysis Cartesian diagram is known that factors that are considered important in accordance with the reality perceived by the customer so that there is a relatively high level of satisfaction on factors clarity services officer, disciplinary service officer, justice of service and comfort environment. While the factors that are considered less important by the customer and in fact not too special in which an increase in attributes in this quadrant can be reconsidered as an influence on the perceived benefits by a very small customer service is the factor procedures, responsibilities attendant service, speed of service and courtesy and hospitality workers.